Ammonia gas mitigation by reactive absorption - Moser, Vitor Moritz; Silva, Marcela Kotsuka; Camara Bastos, Jaci Carlo Schramm (Multi-Science Journal, 2025)
Odors from the decomposition of organic matter in rendering plants, bioenergy facilities, and composting plants cause notable environmental and health impacts in nearby communities due to the significant emission of ammonia gas, making the implementation of mitigation technologies essential. This study aimed to evaluate a pilot-scale reactive absorption column for treating a concentrated stream of ammonia gas and to simulate industrial-scale equipment. A coupled experimental and numerical investigation was conducted; a pilot-scale chemical scrubber was set up, and a 32 experimental design were performed with concentrations of ammonia and sulfuric acid as factors. The results demonstrated effective treatment with removal rates varying from 6.3% to 44.9%, with the limiting factor being the acid concentration in the scrubbing solution. Data were analysed using surface response methodology, and coupled numerical models were employed to determine the mass transfer coefficient and reaction rate constant. These data were regressed numerically and fitted into a microscopic mathematical model that accounted for both gas absorption by the liquid and the chemical reactions; this approach enabled the estimation of key parameters such as specific reaction rates and mass transfer. Finally, numerical studies were carried out to assess industrial-scale behaviour, explore scenarios for scale-up, predict equipment dimensions, and confirm the feasibility of industrial application. Results indicated that the industrial reactive absorption column could treat an ammonia stream flowing at approximately 27,000 m³/h (7.97kg/m3 of NH3) with near 100% efficiency.